2017
DOI: 10.1111/pcn.12618
|View full text |Cite
|
Sign up to set email alerts
|

MEF2C mRNA expression and cognitive function in Japanese patients with Alzheimer's disease

Abstract: MEF2C mRNA expression in leukocytes may be a biological marker for cognitive decline in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 53 publications
2
25
1
Order By: Relevance
“…While some studies showed the opposite results. The mRNA expression of MEF2C was low in Alzheimer's Diseases patients, but Sao et al found no correlation between the methylation level of promoter and mRNA expression of MEF2C. Tsumagari et al found that the hypermethylation of the promoter region was correlated with the higher expression of TBX1 in mononuclear myoblasts and multinuclear myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies showed the opposite results. The mRNA expression of MEF2C was low in Alzheimer's Diseases patients, but Sao et al found no correlation between the methylation level of promoter and mRNA expression of MEF2C. Tsumagari et al found that the hypermethylation of the promoter region was correlated with the higher expression of TBX1 in mononuclear myoblasts and multinuclear myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…Our list of previously published blood transcriptome biomarkers of AD is shown in Table 4 [7][8][9][10][11][12][13][14][15]. The Trem1 mRNA levels tended to increase with age only in the control mouse blood.…”
Section: Blood Transcriptome Biomarkers Of Admentioning
confidence: 99%
“…In addition to the presence of amyloid plaques in the brain parenchyma and intraneuronal neurofibrillary tangles, emerging evidence suggests the existence of additional AD pathophysiological pathways, such as innate immune responses, neuroinflammation, and vascular and cell membrane dysregulation [3][4][5]. Our previous studies suggest that the detection of transcriptome biomarkers related to cell stress and inflammation in the peripheral blood has significant potential as a minimally invasive and inexpensive diagnostic tool for the diagnosis and early detection of developing AD [6][7][8][9][10][11][12][13][14][15]. Although DNA methylation and RNA expression changes in blood might have utility as biomarkers of cognitive dysfunction and brain aging [16,17], the major limitation of blood biomarkers of AD is the lack of a direct correlation with biomarkers in brain tissues.…”
Section: Introductionmentioning
confidence: 97%
“…Antigen presentation (Karch and Goate, 2015) rs2301275 PVR NK and T cell function (Stamm et al, 2018a,b) rs2376866 rs117612135 RELB Dendritic cell differentiation, regulation of adaptive immune response (Zanetti et al, 2003) rs190982 MEF2C B cell proliferation and antigen presentation (Sao et al, 2018) Many other SAD associated genes have also been shown to play vital roles in immune reactivity in the brain. Rare variants in TREM2, which are thought to be loss of function, and increase the risk of developing AD by approximately 2-to 4-fold, were identified by whole-genome sequencing (Sierra et al, 2013;Wolf et al, 2017).…”
Section: Epha1mentioning
confidence: 99%